2007
DOI: 10.1002/rsa.20174
|View full text |Cite
|
Sign up to set email alerts
|

Topological properties of the one dimensional exponential random geometric graph

Abstract: In this paper we study the one dimensional random geometric (random interval) graph when the location of the nodes are independent and exponentially distributed. We derive exact results and limit theorems for the connectivity and other properties associated with this random graph. We show that the asymptotic properties of a graph with a truncated exponential distribution can be obtained using the exponential random geometric graph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In RGGs, n nodes are placed independently at random according to some spatial probability distribution and two nodes can connect by an edge if and only if their distance is less than a critical cutoff r [18]. ERGGs is a special kind of RGGs, it requires the inter-node distance following exponential distribution [24].…”
Section: B Exponential Random Geometric Model For Vanetmentioning
confidence: 99%
See 1 more Smart Citation
“…In RGGs, n nodes are placed independently at random according to some spatial probability distribution and two nodes can connect by an edge if and only if their distance is less than a critical cutoff r [18]. ERGGs is a special kind of RGGs, it requires the inter-node distance following exponential distribution [24].…”
Section: B Exponential Random Geometric Model For Vanetmentioning
confidence: 99%
“…We can see in [17] [19], RGGs are excellent model to describe the communication between nodes in wireless sensor network. The ERGGs is a special kind of RGGs, it requires the inter-node distance following exponential distribution [24]. We are very concerned about the distributions of distance between successive vehicles during analyzing VANETs connectivity [15].…”
Section: Introductionmentioning
confidence: 99%
“…In Gupta et al (2006); Karamchandani et al (2005) the node locations are assumed to be at distances that are i.i.d. exponential from the origin and many topological properties are derived.…”
Section: 2a Topological Propertiesmentioning
confidence: 99%
“…This showed that for n nodes uniformly, independently and identically distributed (i.i.d.) in a disk of area A, with the particular radio transmission range is given by (1).…”
Section: Related Workmentioning
confidence: 99%
“…The goal was to construct a special subgraph, the Restricted Delaunay Graph, that permits efficient routing, based only on local information. In [1,13,18] the authors studied the toplogy and connectivity properties of random geometric graphs.…”
Section: Introductionmentioning
confidence: 99%